EFEKTIVITAS PENGGUNAAN APLIKASI BUSUU UNTUK MENINGKATKAN MAHARAH AL-QIRA’AH DALAM PELAJARAN BAHASA ARAB PADA SISWA DI MAS INSAN KESUMA MADANI - Sutan Bilal Hafidz Al Maulana; Yurmaini; Laila Auni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the process and effectiveness of using the Busuu application in improving maharah al-qira’ah (reading skills) among tenth-grade students at MAS Insan Kesuma Madani. This research employed a qualitative phenomenological approach, with data collected through participant observation, semi-structured interviews, and documentation. Data were analyzed using the Miles & Huberman model, which includes data condensation, data display, and conclusion drawing, while the validity of the data was ensured through source and technique triangulation as well as member checking. The findings show that the use of Busuu in Arabic language learning was carried out in three stages: planning, implementation, and evaluation. During the implementation, Busuu features such as thematic vocabulary, graded reading texts, and automated feedback supported students in improving their reading skills. Indicators of effectiveness identified include improved reading fluency, the ability to understand main ideas and detailed information, the emergence of reading strategies, and increased motivation and learning engagement. Supporting factors of effectiveness include teacher readiness and lesson plan integration, while the main challenges were related to device limitations and unstable internet connectivity. Thus, this study affirms that the use of Busuu can serve as an effective and contextual digital medium to enhance students’ maharah al-qira’ah at MAS Insan Kesuma Madani, while also providing important recommendations for Arabic language teachers in optimizing technology-based learning.